Uwarunkowania aktywności zawodowej osób z ograniczeniami sprawności: czynniki społeczno-demograficzne - Brzezińska, Anna Izabela; Kaczan, Radosław; Piotrowski, Konrad; Sijko, Kamil; Rycielski, Piotr; Wiszejko-Wierzbicka, Dorota (My University, 2008)
The following article presents the goals and assumptions contained in the project entitled “Psychosocial influences concerning disabled people’s professional activity”. The study was conducted in four stages: (1) document analysis and literature review presenting research concerning how disabled people function on the job market; (2) expert opinions, including disabled people; (3) qualitative studies employing Maxqda2 to analyze information gathered from 311 interviews; and (4) quantitative research on a sample of 1498 participants with various types of disabilities (hearing, sight, physical, somatic, and psychological) conducted in 2007. The following article presents the first set of results obtained, referring to connections on a socio- demographic level (place of residence, gender, age, education, and marital status) as well as those isolating disability characteristics (type, level, and genesis) against degree of life satisfaction. Comparisons were executed for five groups with various employment statuses: employed, those looking for employment who had worked before, those looking for employment who had no previous employment experience, previously employed but had no intention of returning to the workforce and those who had never worked and had no intention of becoming employed. Lowest feelings of life satisfaction were among those not looking for employment whereas highest levels of life satisfaction occurred amongst employed participants. Important risk factors: gender (female), age (elderly), low education, marital status (single), place of residence (non-city dwellers), disability (innate and level).
Socio-demographic factors influencing disabled people’s professional activity
Podstawowym celem naszych poszukiwań badawczych było ustalenie, jakie są kompetencje psychospołeczne osób z ograniczoną sprawnością w zakresie podejmowania i utrzymania aktywności zawodowej oraz psychologiczne i społeczno-kulturowe (1) czynniki ryzyka, ograniczające korzystanie z posiadanych zasobów i (2) czynniki ochraniające bądź wzmacniające zasoby i wpływające pozytywnie na funkcjonowanie na rynku pracy. Celem czwartego etapu badań, którego wyniki prezentujemy tutaj, było ustalenie, jakie czynniki związane są z podejmowaniem aktywności zawodowej przez osoby niepełnosprawne oraz z odczuwanym przez nie zadowoleniem z życia. Czynniki te podzieliliśmy na kilka grup: (1) lokalizacyjne, demograficzne i związane z niepełnosprawnością – stanowiły one kryteria doboru grupy badanej, (2) związane z socjalizacją i wychowaniem w okresie dzieciństwa oraz z aktualnymi relacjami społecznymi w rodzinie i poza nią i (3) podmiotowe, związane z kompetencjami osobistymi. Tutaj prezentujemy wyniki dotyczące tylko pierwszego bloku zmiennych.
Keywords: professional activity; disability; life satisfaction; socio-demographic influences